1999
DOI: 10.1089/neu.1999.16.1225
|View full text |Cite
|
Sign up to set email alerts
|

Axonal Cytoskeletal Responses to Nondisruptive Axonal Injury and the Short-Term Effects of Posttraumatic Hypothermia

Abstract: In human diffuse axonal injury (DAI), axons are exposed to transient tensile strain. Over the ensuing several hours, injured axons enter a "pathological cascade" of events that lead to secondary axotomy. Use of animal models of traumatic axonal injury (TAI) has allowed description of a number of pathological changes before axotomy occurs, including structural and functional changes in the axolemma, disorientation, and/or loss of microtubules, either compaction and/or dispersion of neurofilaments together with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 28 publications
1
30
0
Order By: Relevance
“…The use of b-APP and silver staining in this study demonstrated a temporal profile of axonal injury following PBBI, which appeared to respond to the immediate SBC treatments differently. The early axonal injury near the injury core was likely caused by the acute axonal cytoskeletal disruption, which inhibited axoplasmic flow and resulted in b-APP accumulation (Maxwell et al, 1997(Maxwell et al, , 1999. The protective effects of the immediate SBC on reducing PBBI-induced early axonal injury were likely associated with hypothermic protection against axonal cytoskeletal damage via inhibiting calpain-mediated spectrin proteolysis (Buki et al, 1999;Buki and Povlishock, 2006) and ameliorating the loss of axonal microtubules and compaction of neurofilaments (Maxwell et al, 1999) as evidenced in other studies using different traumatic axonal injury models (Buki et al, 1999;Maxwell et al, 1999).…”
Section: Discussionmentioning
confidence: 86%
“…The use of b-APP and silver staining in this study demonstrated a temporal profile of axonal injury following PBBI, which appeared to respond to the immediate SBC treatments differently. The early axonal injury near the injury core was likely caused by the acute axonal cytoskeletal disruption, which inhibited axoplasmic flow and resulted in b-APP accumulation (Maxwell et al, 1997(Maxwell et al, , 1999. The protective effects of the immediate SBC on reducing PBBI-induced early axonal injury were likely associated with hypothermic protection against axonal cytoskeletal damage via inhibiting calpain-mediated spectrin proteolysis (Buki et al, 1999;Buki and Povlishock, 2006) and ameliorating the loss of axonal microtubules and compaction of neurofilaments (Maxwell et al, 1999) as evidenced in other studies using different traumatic axonal injury models (Buki et al, 1999;Maxwell et al, 1999).…”
Section: Discussionmentioning
confidence: 86%
“…Experimental studies of post-traumatic hypothermia suggest a multitude of possible mechanisms for neuroprotection. These include reducing levels of the excitatory amino acid glutamate; decreasing abnormal blood-brain barrier permeability after traumatic and ischemic insults; inhibiting diffuse axonal injury; reducing proinflammatory cytokines interleukin 1-b and tumor necrosis factor-a; inhibiting apoptotic cell death by decreasing both cytochrome c release from dysfunctional mitochondria as well as levels of caspase, a significant initiator of apoptosis [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Additionally, TBI is often characterized by a postinjury catecholamine surge that correlates directly with the severity of brain injury [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…69,70 Previous investigations using this model have greatly improved our understanding of the sequence of neurochemical and ultrastructural events that lead to delayed axotomy, but do not address the specific biomechanical parameters causing axonal damage in TBI. [67][68][69][70][71][72] Furthermore, Bain et al 73 demonstrated in this model that distinct mechanical thresholds exist for morphological compared to electrophysiological damage to the white matter. Less stretch was required to elicit electrophysiological changes (5.5 mm) than morphological signs of damage (6.8 mm).…”
Section: Nerve Stretch Injury Modelmentioning
confidence: 93%